Psychedelic Treatment for Trauma-Related Psychological and Cognitive Impairment Among US Special Operations Forces Veterans. (July 2020) - Davis, Alan K.; Averill, Lynnette A.; Sepeda, Nathan D.; Barsuglia, Joseph P.; Amoroso, Timothy
Background: U.S. Special Operations Forces Veterans are at increased risk for a variety of mental health problems and cognitive impairment associated with military service. Current treatments are lacking in effectiveness and adherence. Therefore, this study examined psychedelic treatment with ibogaine and 5-methoxy-N, N-dimethyltryptamine for trauma-related psychological and cognitive impairment among U.S. Special Operations Forces Veterans. Method: We conducted a survey of Veterans who completed a specific psychedelic clinical program in Mexico between 2017 and 2019. Questions probed retrospective reports of mental health and cognitive functioning during the 30 days before and 30 days after treatment. A total of 65 people completed treatment during this time frame and were eligible for contact. Of these, 51 (78%) completed the survey and were included in data analyses (mean age = 40; male = 96%; married = 55%; Caucasian/White = 92%; Operation Enduring Freedom/Operation Iraqi Freedom Service = 96%). Results: Results indicated significant and very large reductions in retrospective report of suicidal ideation (p < .001; d = −1.9), cognitive impairment (p < .001; d = −2.8), and symptoms of posttraumatic stress disorder (p < .001; d = −3.6), depression (p < .001; d = −3.7), and anxiety (p < .001; d = −3.1). Results also showed a significant and large increase in retrospective report of psychological flexibility (p < .001; d = 2.9) from before-to-after the psychedelic treatment. Increases in the retrospective report of psychological flexibility were strongly associated with retrospective report of reductions in cognitive impairment, and symptoms of posttraumatic stress disorder, depression, and anxiety (rs range −0.61 to −0.75; p < .001). Additionally, most participants rated the psychedelic experiences as one of the top five personally meaningful (84%), spiritually significant (88%), and psychologically insightful (86%) experiences of their lives. Limitations : Several limitations should be considered including the retrospective, self-report, survey design of the study, and the lack of randomization and blinding, thus making these finding preliminary. Conclusion: U.S. Special Operations Forces Veterans may have unique treatment needs because of the sequela of problems associated with repeated trauma exposure and the nature of the exposure. Psychedelic-assisted therapy with these under-researched psychedelics may hold unique promise for this population. However, controlled studies are needed to determine whether this treatment is efficacious in relieving mental health and cognitive impairment among U.S. Special Operations Forces Veterans.